An Old New Friend: Folliculo-Stellate Cells in Pituitary Neuroendocrine Tumors - Nastase, Valeria-Nicoleta; Burcea, Iulia Florentina; Dumitriu-Stan, Roxana Ioana; Ceausu, Amalia Raluca; Zara, Flavia; Poiana, Catalina; Raica, Marius (Cells (Basel, Switzerland), 2025)
Pituitary neuroendocrine tumors (PitNETs) represent a complex pathology based on numerous incompletely elucidated molecular mechanisms. Beyond tumor cells, analyzing the tumor microenvironment may help identify novel prognostic markers and therapies. A key component of this environment is the folliculo-stellate (FS) cell. We examined FS cells in 77 PitNETs obtained by transsphenoidal surgery, using glial fibrillary acidic protein (GFAP) as an immunohistochemical marker. Immunohistochemistry for anterior pituitary hormones and transcription factors was performed to accurately classify the tumors. Our study included 19 somatotroph, 16 mammosomatotroph, 5 plurihormonal PIT-1 positive, 7 corticotroph, 14 gonadotroph, 11 unusual plurihormonal, and 5 null cell PitNETs. FS cells were observed in 55 of the cases, distributed isolated, in small groups or diffuse networks. A considerable number of tumors immunopositive for more than one hormone (including associations between GH/PRL, but also unusual combinations like GH/ACTH) also contained FS cells (p < 0.01), suggesting their involvement in tumor lineages differentiation. In 27 tumors, GFAP-positive cells clustered in highly vascularized areas. Additionally, in 11 of these cases a direct interaction between endothelial cells and FS cells was noted, sustaining their potential role in tumor angiogenesis. Given their complexity, FS cells may be crucial for understanding tumorigenesis mechanisms.